Pengaruh Disiplin Kerja dan Etos Kerja terhadap Kinerja Pegawai pada Badan Kesatuan Bangsa dan Politik Kota Bandung - Mahfud Khoiri; Deden Gunawan; Mira Veranita; Wilma Zuarko Adji (Ekonomis: Journal of Economics and Business, 2022)
The purpose of this study was to prove the effect of work discipline and work ethic on employee performance at the Bandung City Political and National Unity Agency. The National Unity and Political Body of Bandung City has the main task of carrying out supporting functions related to government affairs in the field of national unity and politics. The approach in this study uses quantitative methods in the form of associative (causal). The sample used is all employees, totaling 47 respondents with a non-probability sampling technique, namely a saturated sample, where the entire population is sampled. The data obtained by the researcher used a questionnaire which was distributed to all employees. The data analysis used by the researcher is inferential statistics (parametric) with data feasibility tests including validity and reliability tests, prerequisite tests or basic assumptions of regression, namely residual normality, multicollinearity, heteroscedasticity. Meanwhile, for the hypothesis test, F test, t test, correlation analysis, coefficient of determination analysis, and multiple regression equations were carried out. In this study, it was shown that the work discipline variable had a positive effect on performance with a value of 5.766 and a significant value less than 0.05. The work ethic variable shows a positive effect on performance as indicated by a value of 7.166 and a significant value less than 0.05. The variables of work ethic and work discipline both have a positive influence on employee performance with a value of 25.212 and a significant value of 0.000 <0.05.